Are the Nurses able to Reflect their Undergraduate Education upon the Clinic? The Effect Factors. (13th May 2015) - Calık, Kıymet Yesilcicek; Aktas, Songul; Bulut, Hacer Kobya; Anahar, Elif Ozdas; Erdol, Hacer
Abstract: One of the main problems in the provision of nursing services in Turkey is that nurses are not able to transfer their theoretical knowledge and skills to practice sufficiently. This study aims to uncover the causes of this situation. This descriptive research was carried out with 176 nurses working in five public hospitals in a metropolis in the northeast of Turkey. Numerical and percentage values were used in the evaluation of data. As a result, nurses' clinical working environment (72.7%), the clinic's physical structure and hardware (75.0%), health care team members (80.1%), management's attitude (65.9%) and institutional / health policies (67.6%) were found to be significantly influential in transferring their training to clinics.